1993
DOI: 10.1002/art.1780360104
|View full text |Cite
|
Sign up to set email alerts
|

HLA–DR4 subtypes in new zealand polynesians. predominance of dw13 in the healthy population and association of dw15 with rheumatoid arthritis

Abstract: Objective. To analyze HLA–DR4 alleles in New Zealand Polynesians with rheumatoid arthritis (RA).Methods. Thirty Polynesians and 30 Caucasians with RA, as well as 65 Polynesian and 60 Caucasian healthy blood donors, were DR4 subtyped using the polymerase chain reaction and sequence‐specific oligonucleotide probes.Results.The frequency of DR4 (DRB1*04) was increased in both Polynesian (P <0.001) and Caucasian (P <0.005) RA patients compared with race‐matched controls. Dw4 (DRB1*0401) was detected in 15 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The fact that DRB1 *0403 was the most prevalent DR4 subtype in controls could account for the weak association of the disease with DR4 and for the relatively lower RA prevalence (0.1-0.5%) found in Chile12 (Riedemann P, personal communication). This inference is similar to that made previously in New Zealand Polynesians 13. Allelic combinations involving *0401/*0401 or *0401/*0404, which are strongly associated with RA severity,2 3 14 were present in seven (5%) of our patients and in none of the controls.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that DRB1 *0403 was the most prevalent DR4 subtype in controls could account for the weak association of the disease with DR4 and for the relatively lower RA prevalence (0.1-0.5%) found in Chile12 (Riedemann P, personal communication). This inference is similar to that made previously in New Zealand Polynesians 13. Allelic combinations involving *0401/*0401 or *0401/*0404, which are strongly associated with RA severity,2 3 14 were present in seven (5%) of our patients and in none of the controls.…”
Section: Discussionsupporting
confidence: 92%
“…36 This compares with control data from a previous study from our institution that revealed shared epitope positive HLA-DRB*01/*04 alleles in 40% of white subjects and 26% of Polynesians within a New Zealand population 36. We found no significant difference in carriage of the shared epitope between those with MR erosions (82.4%) and those without (69.6%).…”
Section: Discussionsupporting
confidence: 55%
“…The introduction of DNA typing to HLA typing elucidated the role of HLA in the pathogenesis of RA. HLA-DRB1*0401, DRB1*0404, DRB1*0405 and DRB1*0408 were reported to be associated with RA in Caucasian populations [7, 53, 54, 55]and DRB1*0405 in Japanese [56], Taiwanese [57], Korean [8], Israeli [58], New Zealand-Polynesian [59]and Spanish [12]populations. DRB1*0402 and DRB1*0403 have never been reported to be associated with RA in any ethnic group.…”
Section: Discussionmentioning
confidence: 99%